Pragmatism and Human Flourishing: Putman and Rorty - Rosales Rodríguez, Amán (Estudios de Filosofía, 2005)
In this paper an answer is given to the question: “what does ‘human flourishing’ mean in the current ‘neopragmatist’ perspective?”. The exposition is based on the ideas of H. Putnam and R. Rorty, who propose two similar and yet different approaches to the question. The consideration of these two philosophical variants show that contemporary pragmatism is not a undifferentiated block of opinions, and that it a mistake to associate the ideas of both Putnam and Rorty with a pernicious relativism or a radical skepticism. Some comments on the current function of Philosophy according to both authors close the article.